2016
DOI: 10.1002/aelm.201500368
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Band and Hopping Electron Transport in SrTiO3

Abstract: SrTiO3 (STO) is a model system for studying oxide electronic devices. This work examines the electronic transport through a heterostructure comprising an acceptor (Fe)‐doped STO layer on a donor (Nb)‐doped STO substrate. This is done by fitting the steady‐state current–voltage (I–V) curve measured at ambient temperature to numerical solutions of the drift‐diffusion equations of itinerant (i.e., free) electrons and holes (band conduction) and localized electrons hopping through defect states within the bandgap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Therefore, the contribution of electron hopping between V 4+ /V 3+ couple to total electronic conductivity is likely to be limited. Instead, electronic transport is expected to occur mainly by either itinerant electrons in the conduction band formed by Ti cations, or by hopping of localized electrons between Ti 4+ /Ti 3+ couples, or by a combination of mechanisms . Reducing the oxygen partial pressure results in an increasing fraction of Ti 3+ cations (i.e., charge carriers associated with Ti cations); even if [Ti 3+ ] is still lower or comparable to [V 4+ ], this is accompanied by a smooth increase of the conductivity for compositions with y ≥0.7 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the contribution of electron hopping between V 4+ /V 3+ couple to total electronic conductivity is likely to be limited. Instead, electronic transport is expected to occur mainly by either itinerant electrons in the conduction band formed by Ti cations, or by hopping of localized electrons between Ti 4+ /Ti 3+ couples, or by a combination of mechanisms . Reducing the oxygen partial pressure results in an increasing fraction of Ti 3+ cations (i.e., charge carriers associated with Ti cations); even if [Ti 3+ ] is still lower or comparable to [V 4+ ], this is accompanied by a smooth increase of the conductivity for compositions with y ≥0.7 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar p-type to n-type inversion was observed in Fe-doped SrTiO3 thin films on Nb-doped SrTiO3 (n-type) substrates, as reported elsewhere. 27 Domen et al reported a similar effect in La5Ti2CuS5O7 photoelectrodes that displayed ambipolar photocurrents depending on the current collector electrode on which they were deposited. 28 Of all the photoelectrodes in this study, the Zn-doped one (red curve) displayed the lowest onset potential, but also the lowest plateau photocurrent at high potentials (> 1.4 VRHE).…”
mentioning
confidence: 83%
“…The oxygen vacancies with relatively low formation energies can also play a critical role in determining the surface and electronic properties of SrTiO 3 . Experimental and theoretical studies have proved that the lowest energy charge state for oxygen vacancies with chemical stability is +2 in the vast majority of conditions [5,14,15]. Based on the assumption that oxygen vacancies in SrTiO 3 carry positive charges, Chiang et al proposed that oxygen vacancies provide the dominant contribution to tilting grain boundaries by the positive core charge in SrTiO 3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation barrier hopping has been found to be prevailing in the conduction mechanism of crystals [10]. The analysis of Fe:STO/Nb:STO heterostructure shows that electron hopping through localized defect states such as oxygen vacancies within the band gap is dominant at reverse and low forward bias [14]. Using anelastic relaxation measurements, two main relaxation mechanisms in oxygen deficient SrTiO 3 are identified with hopping of isolated oxygen vacancies over a barrier of 0.60 eV and reorientation of pairs of vacancies involving a barrier of 0.97 eV [15].…”
Section: Introductionmentioning
confidence: 99%